LAYANAN PERBANKAN SYARIAH BERBASIS TEKNOLOGI SEBAGAI WUJUD PENERAPAN GREEN BANKING - Bagas Oges Bryan Pratama; Muhamad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
Technology-based islamic banking service innovation is a technological innovation whose operational activities no longer use humans but use automatic and computer-controlled methods. Green banking is an environmentally sound bank operational activity as an effort to be responsible for environmental sustainability. The method used in this research is descriptive qualitative analysis, where all the data generated is presented in the form of a description, namely an overview of the research results. The results of the study show that innovation in technology based Islamic banking services is one of the efforts of Islamic banking in implementing green banking